INTENSITAS PEMBERITAAN KEGIATAN KEAGAMAAN PADA SURAT KABAR POSMETRO ROHIL - Putra, Heri Rahmatsyah; Armi, Fadhlur Rahman (UIN Mataram, 2021)
The purpose of this study is to find out the intensity of the reports on Posmetro Rohil's newspaper on religious activities. It attracts the attention of the writer because Posmetro Rohil is a newspaper in the middle of Rokan Hilir's society which is mostly fanatical of religious activities. The method used in this research is a qualitative descriptive with data acquisition through observation, interview, and documentation. It is known from this study that the factor affecting the story of Posmetro Rohil is based on an individual factor that describes that media management personnel do not have a higher tendency towards religious activity. Then outside media factors like resource and media revenue. And the last ideological factor, Posmetro is an independent newspaper and does not bring interest to a particular group. Although news about religious activity is news that tends to attract interest in reading society.